Relay OCR dan GFR ANALISIS KINERJA OVER CURRENT RELAY (OCR) & GROUND FAULT RELAY (GFR) PADA PENYULANG 20KV GB5 ULTG GORONTALO MENGGUNAKAN ALAT UJI CMC 356 - Amali, Kamil; Damogalad, Muhamad Rifai; Yusuf, Taufik Ismail; Harun, Ervan Hasan; Tolango, Ade Irawaty (Program Vokasi-Universitas Negeri Gorontalo, 2024)
This research was conducted to test the reliability of the performance of the OCR-GFR relay whether it complies with the settings or not during field testing and to find out a comparative analysis of the performance of theoretical calculations with the results of field testing using the CMC 356 test equipment. This research uses a descriptive method. This research aims to determine whether the performance of the OCR–GFR relay that is being used is still good performance or suitable for use. And the tests carried out are pick up and drop off tests and characteristic tests. The results of the OCR pick-up and drop-off relay test were 1.2 A and the drop-off was 1.134 A. Meanwhile, for the GFR relay the pickup relay was 0.20 A and the drop-off was 185.0 mA. The results of the pickup and drop-off tests can conclude that the relay works according to its settings. Meanwhile, for field testing, the OCR relay characteristics at 1.5 times the setting current are 3.627 s and the theoretical calculation results are 3.697 s. For the GFR relay, the field test results obtained were 1.5 times the setting current, namely 1.981 s, and the theoretical calculation results were 1.977 s. This means that the test results are close to the calculated values. This shows that the Micom P142 OCR/GFR Relay tested is still in good performance.